Imagining evidence, fictioning truth - revisiting (courtesy of O. J. Simpson) expert evidence in the Chamberlain case - A. Howe (Law Text Culture, 1997)
Connoisseurs of bizarre criminal cases must have been revelling. Could there really have been any doubt that the two 'trials of the century' would hit the press in the same week, despite a time lapse of thirteen years? On 1 October 1995 the Australian press reported that a third 'limited scale' coronial inquiry into the death of Azaria Chamberlain was about to be opened in the Northern Territory in order to 'clear the public record'. This was to be Australia's eighth judicial inquiry into the marathon miscarriage of justice which was the Chamberlain case, the seven previous inquiries having failed, apparently, to clear the public record. Three days later the media reported that the jury had reached its verdict in the OJ Simpson trial, North America's latest celebrity (read: media farce) murder trial.